Immersive Intelligence in Practice: Reframing Media Production Pedagogy for the AI Era. - Arabi, Afif (2025)
Artificial Intelligence (AI) and Immersive Technologies (Virtual, Augmented, and Mixed Reality) are reshaping how stories are developed, captured, and delivered — pushing the media production industry into a new era. For media production educators, this evolution presents both a challenge and an opportunity: how can university programs evolve fast enough to keep graduates professionally relevant and critically literate in this changing landscape? This research investigates the accelerating adoption of AI and immersive tools across the media production pipeline — from generative storyboarding in pre-production to real-time rendering on virtual sets and automated post-production workflows. Drawing on industry case studies and emerging educational practices, the study examines where professional innovation is outpacing curriculum design and how this gap jeopardizes student readiness. Key barriers are explored, including the high cost of advanced technologies (e.g., LED stages), limited faculty training, and outdated pedagogical models. The research proposes a proactive framework tailored for media production educators: redesigning curricula with AI proficiency along with AI-resilient assignments that foreground human creativity and ethical responsibility, investing in scalable production labs, establishing clear guidelines for responsible AI usage, and forging partnerships with studios and tech companies to provide meaningful access to tools for experiential learning. While these technologies promise to enhance student engagement and build critical media production software skills, they also raise risks — such as academic dishonesty, over-reliance on automation, and threats to creative authorship. Media production educators are uniquely positioned not only to teach tool fluency but also to shape how this technology is harnessed in fostering reflective, ethical practitioners who can lead creative innovation in the digital media age: not just to mirror industry, but to question and guide its trajectory. By adopting an “AI-first” pedagogical approach grounded in critical thinking, storytelling, and creativity, educators can ensure students are not just prepared for the future — but empowered to shape it. Keywords: Media Production Pedagogy, AI Integration, Immersive Technologies, Curriculum Innovation, Digital Literacy, Technological Pedagogical Content Knowledge, Practice-Based Learning